Ответ:
∅
Объяснение:
[tex]\frac{2(x-2)-3(x+6)}{6} = 5 - \frac{x-1}{6}\\\\\\frac{2x-4-3x-18}{6} = 5 - \frac{x-1}{6}\\ \\ \frac{-x-22}{6} + \frac{x-1}{6} = 5\\ \\ \frac{-x-22+x-1}{6} = 5\\ \\ \frac{-23}{6} = 5\\ \\-23 = 30 \\ -23 \neq 30\\\\[/tex]
Відповідь : Рівняння немає розвязку, ∅
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
∅
Объяснение:
[tex]\frac{2(x-2)-3(x+6)}{6} = 5 - \frac{x-1}{6}\\\\\\frac{2x-4-3x-18}{6} = 5 - \frac{x-1}{6}\\ \\ \frac{-x-22}{6} + \frac{x-1}{6} = 5\\ \\ \frac{-x-22+x-1}{6} = 5\\ \\ \frac{-23}{6} = 5\\ \\-23 = 30 \\ -23 \neq 30\\\\[/tex]
Відповідь : Рівняння немає розвязку, ∅